2023
DOI: 10.1021/acsanm.2c04144
|View full text |Cite
|
Sign up to set email alerts
|

Metallogels from Silver Nanoparticles and Peptide Nanofibers as Antimicrobial Surfaces

Abstract: Peptide amphiphiles (PAs) are elusive candidates to construct soft materials possessing various functionalities, including potent antimicrobial activity. It is imperative to look for a broadspectrum antibiotic against which the genesis of drug resistance is difficult. Herein, a histidine-based PA is found to form a transparent metallohydrogel when AgNO 3 is added to a hot solution of the PA in 2:1 (PA/AgNO 3 ) molar ratio. Exposure to 365 nm UV lamp results in blue light-emitting silver nanocluster (NC) format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…ROS generated inside the cells leads to oxidative stress and DNA damage, finally causing cell death. 56,57 As discussed earlier, the increasing amount of CD-AgNP increased the intracellular ROS production, and it is clear from Figure S9a that at MIC an elevated level of ROS in the cells was detected. Therefore, it can be concluded that the complete killing of bacteria by CD-AgNP is attained by a mixed pathway of membrane rupture and intracellular ROS production (Figure 8a).…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…ROS generated inside the cells leads to oxidative stress and DNA damage, finally causing cell death. 56,57 As discussed earlier, the increasing amount of CD-AgNP increased the intracellular ROS production, and it is clear from Figure S9a that at MIC an elevated level of ROS in the cells was detected. Therefore, it can be concluded that the complete killing of bacteria by CD-AgNP is attained by a mixed pathway of membrane rupture and intracellular ROS production (Figure 8a).…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…CFUs observations of the metallogel-treated cell culture in TGE-agar plates evidentially demonstrated the cell viability and also confirmed that all the metallogels have growth inhibition ability but are not fatal to the bacteria cells. In general, metal ions exhibit diverse antimicrobial activities, and these properties have been recognized throughout the history of medicine and healthcare. In this study, the metallogels showed antimicrobial activity against both Gram-positive and Gram-negative bacteria . However, the effectiveness of antimicrobial activity varies between metallogels. , In the present work, it was found that Ni­(II)-metallogel showed slight antimicrobial efficiency compared to Co­(II)-metallogel and Zn­(II)-metallogel of azelaic acid used as the low molecular weight organic gelator.…”
Section: Resultsmentioning
confidence: 53%
“…hydrogen bonding interaction, van der Waals forces, dipole–dipole, charge transfer, π–π stacking, etc., are established in literature. Integration of metal ion with the gelators proposes a noteworthy platform to functionalize soft materials with added superior beneficial functionalities . Few celebrated practical applications of gels such as nonlinear optics, , artificial light-harvesting systems, , molecular sensing, , biomedical applications, drug delivery, tissue engineering, , cell imaging, antibacterial and antifungal activity, 3D printing, magnetism, , catalysis, , electronics, light emitting diodes, biotechnology, , etc. are recognized in the scientific domain.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that antibiotics can kill bacteria either by generation of reactive oxygenase species (ROS) or by specific mechanisms of action. 51,52 To explore the effectiveness of the hydrogels as antibiotics a study is designed to generate ROS through synergistic interaction between antibiotics and ROS producing materials. 51 For the above-mentioned study E. coli is treated with different concentrations of the CP1 hydrogel at 10-200 mg mL À1 and 2 0 ,7 0 -dichlorodihydrofluorescein diacetate (DCFDA) is used as the probe.…”
Section: Ros Generation Studymentioning
confidence: 99%
“…51,52 To explore the effectiveness of the hydrogels as antibiotics a study is designed to generate ROS through synergistic interaction between antibiotics and ROS producing materials. 51 For the above-mentioned study E. coli is treated with different concentrations of the CP1 hydrogel at 10-200 mg mL À1 and 2 0 ,7 0 -dichlorodihydrofluorescein diacetate (DCFDA) is used as the probe. DCFDA is a non-fluorescent dye converted into fluorescent 2 0 ,7 0 -dichlorodihydrofluorescein (DCF) in the presence of ROS to measure the efficiency of the hydrogel.…”
Section: Ros Generation Studymentioning
confidence: 99%